Uncontrolled asthma determinants in overweight and obese adults - Vitaly I. Kupaev; Olga V. Sazonova; Maria S. Nurdina; Lyubov M. Borodina; Mikhail Yu. Gavryushin; Dmitry O. Gorbachev (Russian Open Medical Journal)
Relevance of the research — epidemiological and clinical studies in recent years confirmed the existence of a bronchial asthma (BA) phenotype associated with obesity. In the current literature, obesity is considered a possible risk factor for the development of BA. Nonetheless, the factors contributing to the uncontrolled course of BA among overweight patients need to be elucidated. The need for a personalized approach to patient management is reflected in the latest edition of the international consensus document on the asthma treatment – GINA (Global Initiative for Asthma: Global Strategy for Asthma Management and Prevention). Despite substantial number of epidemiological studies on the prevalence of BA in obese patients, the threshold values of major risk factors for the development of uncontrolled BA (vitamin D, IL-17, IL-10, BMI; intake of total fat, carbohydrates and cholesterol) remain unclear. Objective: to identify the risk of developing an uncontrolled course of BA depending on the levels of IL-17, IL-10 and vitamin D; dietary characteristics (intake of total fat, cholesterol and carbohydrates); and body mass index (BMI). Material and methods — The study involved 79 patients with an established diagnosis of BA, 18-69 years old. Patients were split among three groups according to their BMI values. Group I included 27 patients with normal body weight (BMI: 18.5-24.9 kg/m2), 56 (42-61) years of age. Group II comprised 28 overweight patients (BMI: 25-30 kg/m2), 57 (50.5-63.5) years of age; Group III encompassed 24 obese patients (BMI≥30 kg/m2), 58 (54-65) years of age. Results — the risk of developing uncontrolled BA increased by 1.8 times with increase of a total fat intake (95% CI: 1.28-2.72; p=0.001); by 5.7 times with BMI>26.7 kg/m2 (95% CI:2.05-15.92; p<0.001); by 5.2 times with IL-17 level >83.5 pg/mL (95% CI:1.71-15.8; p=0.003); by 8.32 times with vitamin D content <24.5 ng/mL (95% CI: 2.9-23.72; p<0.001). Conclusion — patients with BMI>26.7 kg/m2, vitamin D deficiency (i.e., vitamin D content <24.5 ng/mL), IL-17 content >83.5 pg/mL, as well as excessive consumption of total fat, carbohydrates and cholesterol, could be attributed to the risk group for developing an uncontrolled BA.